Long-term successfull treatment of patient with history of Systemic Lupus Erythematosus complicated with Acute Myocarditis and Dilated Cardiomyopathy – case report - Ziomek, Mateusz; Bożym, Aleksandra; Lis, Paulina; Kaźmierski, Wojciech; Jurek, Jakub; Ziobro, Anna; Kamińska, Alicja; Kozłowski, Jakub; Żaczek, Bartłomiej (Journal of Education, Health and Sport, 2024)
Introduction and aim. Systemic lupus erythematosus (SLE) is a chronic, autoimmune disorder that may affect every organ. The use of immunosuppression has changed a natural course of the disease. Thereupon mortality in SLE is not only associated with implications of disease activity and its impact on cardiovascular system but also with treatment-related complications like cytopenia or increased risk of infection, which can lead to a life-threatening sepsis. Description of the case. We present a case of a 60-year-old Caucasian female patient with a long-time history of active SLE, who has first developed nephrotic syndrome and then acute lupus myocarditis (LM) complicated by dilated cardiomyopathy. Conclusion: The appearance of LM and its complications seem to be a landmark event in the further course of disease.